2020
DOI: 10.32473/ufjur.v21i2.108770
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Support the Survival of Serum-dependent cells in vitro

Abstract: Extracellular vesicles (EVs) are 30-150 nm in diameter and are released by cells into the extracellular environment. They facilitate intercellular communication and may be involved in cell survival. Although serum-dependent cells are not obviously affected by depletion of EVs from the serum, we previously reported that cells in serum that contain EVs were more resistant to the drugs, enoxacin and bis-enoxacin, compared to cells in serum without EVs. This change in resistance led us to examine whether EVs are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, it was found that 4T1 and RAW264.7 cells could grow in serum‐free media supplemented with FBS‐EVs. In fact, while these two cell lines were not able to proliferate in serum‐free media, their viability and cell proliferation increased when FBS‐derived EVs were added to serum‐free media (Christy et al., 2020). Moreover, Lehrich et al.…”
Section: The Unsuspected Functions Of Fbs‐derived Evs In Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was found that 4T1 and RAW264.7 cells could grow in serum‐free media supplemented with FBS‐EVs. In fact, while these two cell lines were not able to proliferate in serum‐free media, their viability and cell proliferation increased when FBS‐derived EVs were added to serum‐free media (Christy et al., 2020). Moreover, Lehrich et al.…”
Section: The Unsuspected Functions Of Fbs‐derived Evs In Cell Culturesmentioning
confidence: 99%
“…Murine breast cancer cells (4T1) and murine macrophages (RAW264.7) are two cell lines that require the presence of FBS in order to be maintained in culture (Christy et al., 2020). However, it was found that 4T1 and RAW264.7 cells could grow in serum‐free media supplemented with FBS‐EVs.…”
Section: The Unsuspected Functions Of Fbs‐derived Evs In Cell Culturesmentioning
confidence: 99%